Online Blended Learning Model to Improve Learning Independence and Learning Outcomes of High School Students - Hendrik Karewangan; Apriani Sulu Parubak; Radite Yogaswara (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2025)
The shift to online learning during the COVID-19 pandemic has challenged students’ ability to learn independently, highlighting the need for effective teaching models to support both autonomy and achievement. This study aims to evaluate the effectiveness of a blended learning model in improving learning independence and chemistry learning outcomes among XI-grade science students at SMA Zion. A classroom action research (CAR) design was employed over two cycles, each comprising planning, action, observation, and reflection phases. The intervention integrated synchronous (real-time online) and asynchronous (independent) learning activities. Thirty-four students participated. Learning independence was measured using a questionnaire, and learning outcomes were assessed through multiple-choice tests on hydrocarbon compounds. In Cycle I, students exhibited low learning independence (57.71%) and achievement (29.41% reached the minimum completion standard). Following targeted improvements such as learning journals, motivational strategies, and instructional videos in Cycle II, both indicators improved markedly: learning independence rose to 76.94%, and 82.35% of students met the minimum standard. The findings demonstrate that the blended learning model significantly enhances both learning independence and academic achievement, emphasizing the importance of innovative, adaptable pedagogical strategies in online education settings.